PERLINDUNGAN HUKUM PIDANA TERHADAP ANAK DAN PEREMPUAN SEBAGAI KORBAN KEKERASAN SEKSUAL DI ERA DIGITAL: Criminal Law Protection for Children and Women as Victims Of Sexual Violence in the Digital Era - Lestari, B. Farhana Kurnia; Sofiana, Ulya; Jiwantara, Firzhal Arzhi (Ganec Swara, 2026)
The development of information technology has brought both positive and negative impacts on society. One of the negative impacts currently rampant is the rise of sexual violence against children and women through digital media. This study aims to analyze the forms of criminal law protection for children and women as victims of sexual violence in the digital era, the factors causing the increase in such crimes, and the effectiveness of law enforcement in Indonesia. The research method used is normative legal research with statutory and conceptual approaches. The results indicate that legal protection for children and women has been regulated in several laws such as Law Number 12 of 2022 concerning Sexual Violence Crimes, the Child Protection Law, and the Electronic Information and Transactions Law. However, its implementation still faces various obstacles, including low public legal awareness, patriarchal culture, weak digital supervision, and suboptimal law enforcement against perpetrators. Therefore, strengthening regulations, public education, and inter-agency synergy are necessary to provide maximum legal protection for children and women